Penggunaan Transformasi Digital Bisnis Untuk Para Pelaku UMKM Kuliner - Rachmat Adiaz Arrofi; Rahman Ajie; Tata Sutabri (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Digital transformation has become a necessity in today's modern era, including for Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector. With increasing internet access and technology penetration at all levels of society, the use of digital technology in business operations has now become standard. For culinary MSMEs, digital transformation does not only mean having an online presence through a website or social media but also involves digitizing business processes, marketing, financial management, and customer service. The benefits offered through this transformation include increasing efficiency, achieving wider markets, and increasing competitiveness in an increasingly competitive market. In addition, with the existence of e-commerce platforms and application-based food delivery services, culinary MSMEs have gained access to consumers who were previously difficult to reach. However, challenges such as limited digital literacy, initial investment, and adapting to business culture remain obstacles. However, with the support of training, education, and collaboration between stakeholders, the potential for utilizing digital transformation by culinary MSMEs can be optimized to encourage economic growth and innovation in this sector.